Exploring COVID-19 disinformation through the lens of modality - Woon, Dilys Ting Ying (Nanyang Technological University, 2021)
This study investigates the role of multimodal disinformation and fact-checks on message credibility, and the intention to share disinformation online. It also considers the mediating role of message credibility between fact-check multimodality and intention to share. With the rise of disinformation during the COVID-19 pandemic, more fact-checks have emerged to combat misperceptions. Yet, modalities of fact-checks have been called into question, with conflicting literature about the effectiveness of textual (monomodal) versus text + visual (multimodal) fact-checks. Using the Heuristic Systematic Model (HSM) as a theoretical framework to control for plausible motivational and cognitive variables that could impact credibility perceptions, this study features a 2 (disinformation: monomodal vs. multimodal) x 2 (fact-check: monomodal vs. multimodal) factorial design conducted on a Singapore sample (N = 205). The results show that multimodal fact-checks are more effective than monomodal fact-checks in debunking disinformation, providing evidence that supplementary visuals are especially effective in reducing credibility. The positive impact of fact-check multimodality on disinformation sharing was fully mediated by message credibility. The results suggest that multimodal fact-checks could be useful triggers for individuals to engage in systematic re-processing of disinformation. Further implications about the role of modality in disinformation, fact-checks and credibility are discussed.